Free convection from a partially heated circular cylinder inside a square enclosure. (2015) - Rabani, Ramin; Talebi, Shahram
In this paper, natural convection heat transfer inside a square enclosure containing a circular cylinder is investigated by thermal lattice Boltzmann method (TLBM). All walls of enclosure are maintained in cold temperature. A part of the cylinder wall is maintained in hot temperature and the rest of it is insulated. This part can be located in top, down, or side position of the cylinder. The circular cylinder is placed at the middle of the square enclosure. The ratio of radius to the length of enclosure is 0.2. The Rayleigh numbers 10 4 and 10 5 are used for solving the problem. Isothermal lines, streamlines, local and average Nusselt number, and average temperature at different states are recorded. The results show that the heating position causes the flow pattern to be changed and vortices to be different. Rayleigh number 10 4 generates no natural strong flow. The Nusselt number variation on the top and bottom walls of enclosure is maximum and minimum in all three states of partial heating, respectively. Furthermore, the heating from the bottom of cylinder has more average temperature than that of two other states of partial heating.